3D Interconnected Networks of Graphene and Flower‐Like Cobalt Oxide Microstructures with Improved Lithium Storage. Issue 1 (16th October 2015) - Binitha, Gangaja; Ashish, Ajithan G.; Ramasubramonian, Deivanayagam; Manikandan, Palanisamy; Shaijumon, Manikoth M.
Abstract : A reduced graphene oxide (rGO)‐based 3D architecture with unique flower‐like cobalt oxide microstructures, uniformly embedded in a graphene hydrogel matrix (CoO–GHG) resulting in completely interconnected structures, is fabricated. The self‐assembled 3D architecture with improved porosity and conductivity exhibits excellent electrochemical performance as an anode for lithium‐ion batteries, with high reversible specific capacity (1010 mAh g −1 over 100 cycles), a long cycling lifetime, and good rate capability. The exceptional performance results from the unique 3D structure of the hybrid CoO–GHG, with highly dispersed flower‐like CoO on a conducting graphene network, providing more accessible surface sites for large lithiation/delithiation with minimum volume expansion and imparting good conductivity and short diffusion length for Li + ions. Electrochemical studies demonstrate that these 3D architectured electrodes are promising as efficient anodes for high‐performance lithium‐ion battery devices. Abstract : A completely interconnected 3D reduced graphene oxide–cobalt oxide composite material with unique flower‐like cobalt oxide microstructures uniformly embedded in a graphene hydrogel matrix is fabricated. The resulting synergistic improvement of porosity and conductivity of the composite material leads to significantly enhanced electrochemical performance as an anode for lithium‐ion batteries.